Reestructuración técnico administrativa en la empresa Distrifertil S.A.S. (2020)
The degree work presented below is based on the Reestructuracuón técnico-administrativa de la empresa Distrifertil S.A.S, which is located in the city of Bogotá and its main economic activity is the manufacture of inorganic and organic fertilizers; In this project, improvement proposals will be made for their different areas that will achieve greater productivity effectively and create a differentiating factor in the market compared to the competition. To carry out the vital restructuring is to make a diagnosis of the current situation of the organization as well as the sector of diagnosis in sector analysis tools (PESTAL) at national and departmental level, (DOFA matrix) to carry out a internal analysis, which allows identifying strengths and weaknesses at an internal level, as well as opportunities and threats at an external level and establishing different proposals for improvement.